Quiet Eye research - Joan Vickers on target - Ernst-Joachim Hossner (Ed.) (Bern Open Publishing, 2016)
In this target article (TA; CISS2016_100), Joan Vickers gives an overview of 20 years of research on her discovery that a relatively long lasting fixation before movement initiation enhances complex-motor performance, the so-called Quiet Eye (QE) phenomenon. Vickers' main article (CISS2016_101) is the focus of sixteen peer commentaries (CISS2016_102 - CISS2016_117), authored by sport scientists with a special focus on the QE (Causer; Farrow & Panchuk; Klostermann, Vater & Kredel; Mann, Wright & Janelle; Schorer, Tirp & Rienhoff; Williams; Wilson, Wood & Vine), by sport scientists with different research foci (Baker & Wattie; Davids & Araujo; Frank & Schack; Helsen, Levin, Ziv & Davare; Rodrigues & Navarro), and by experts in human perception from disciplines beyond sport science (Foulsham; Gegenfurtner & Szulewski; Spering & Schütz; Watson & Enns). Finally, critiques, suggestions, and extensions brought forward by the commentators are acknowledged by Vickers in her closing response (CISS2016_118).